Pengaruh Keberhasilan Sekolah Rintisan Google dan Kepemimpinan Transformasional Terhadap Mutu Sekolah Di SMP Negeri Se-Kabupaten Dharmasraya - Leni Oktawira; Asmendri Asmendri; David David; Muhammad Fazis; Elda Herlina (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to determine the influence of Google Reference School Success and transformational leadership on school quality at public junior high schools in Dharmasraya Regency. This study used a quantitative approach with a survey method. The population consisted of 101 teachers and educational staff from schools implementing the Google Reference School program, while 81 respondents were selected using Simple Random Sampling. Data were collected through questionnaires on Google Reference School Success, transformational leadership, and school quality. Data analysis employed multiple linear regression analysis after fulfilling classical assumption tests. The results showed that Google Reference School Success and transformational leadership simultaneously had a positive and significant effect on school quality. Partially, transformational leadership had a more dominant contribution to improving school quality. The coefficient of determination indicated that both variables contributed significantly to the improvement of educational quality in the digital era. These findings emphasize that digital transformation supported by visionary leadership is an important factor in creating sustainable school quality improvement.